Pengaruh Event Syncrhronize Festival 2024 terhadap Peningkatan Citra dalam Program "Green Movement" - Sallam , Rizki Agus; M, Rory Apsa; Alwasih, Alwasih; Fikri, Muhammad Adzkaar; Sari, Bella Pusphita; El Adawiyah, Sadiyah (Innovative: Journal Of Social Science Research, 2025)
Synchronize Festival is an annual music festival in Indonesia featuring various music genres and has become one of the largest in Southeast Asia. Since its inception, the festival not only offers entertainment but also introduces the Green Movement program aimed at raising environmental awareness. This study aims to analyze the influence and effectiveness of the Green Movement program on enhancing the image of Synchronize Festival 2024. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 100 respondents, and analysis using Structural Equation Modeling (SEM) with the SMARTPLS application. The results show that the Green Movement program, which includes waste reduction, the use of tumblers, and promoting eco-friendly transportation, has a significant impact on improving the festival's image in the eyes of the audience. The program successfully reduced festival waste and plastic bottle usage, as well as increased visitor participation in the Bike to Synchronize program. Additionally, the study found that the majority of the festival attendees were young individuals with a high environmental awareness, which contributed to the success of the program. The structural model evaluation results indicate that the Green Movement explains 68.2% of the improvement in the festival's image.Thus, the Green Movement program proves effective in strengthening Synchronize Festival's image as an environmentally friendly music event. This study concludes that this initiative not only provides positive impacts on the environment but can also serve as a model for similar events in the future.